African yearbook of international law = Annuaire african de droit international. Vol. 20, 2013-2014. - Yusuf, Abdulqawi A. (Leiden : Brill / Martinus Nijhoff, 2015)
Founded in 1993, the African Yearbook, now published under the auspices of the African Foundation for International Law, is the only scholarly publication devoted exclusively to the study, development, dissemination and wider appreciation of international law in Africa as a whole. Through the scholarly analysis of international legal issues relevant to the African continent, the yearbook also contributes to the acceptance of, and respect for the rule of law in intra-African relations and for principles of international law generally. Its uniqueness, however, goes beyond these factors, for, through its special themes and general articles, the yearbook has succeeded in serving as an intellectual forum where the development of international law is viewed as being integral to Africa's own development. 00In addition to scholarly analysis of contemporary legal issues, the Yearbook provides access to documents from African international organizations and regularly publishes resolutions and decisions of regional and sub-regional organizations. Also included in the content are resolutions and decisions of regional and sub-regional organizations as well as the conventions, protocols, and declarations adopted by pan-African agencies. 00Through the study and analysis of emerging legal issues of particular reveleance to Africa, such as the creation of viable continental institutions capable of promoting unity and security for the peoples of the continent, the effective protection of human rights, the need for accountability for mass killings and massive violations of the rule of law, the promotion of a rule-based democratic culture, the role of African countries in a globalizing world economy and in international trade relations, the Yearbook strives to be responsive to the intellectual needs of African countries in the area of international law, and to the continuing struggle for creating an environment conducive to the rule of law throughout the continent.
Keywords: International law -- Africa